A real-time imaging approach to quantify dendritic cell internalization for immunogenicity risk assessment of biotherapeutics - Yin, Zhaojun; Tran, Peter; Guerrero, Joyce; Low, Justin; Xie, Qing; Peng, Kun (Frontiers in Immunology, 2025)
The presence of treatment-emergent anti-drug antibodies (ADAs) can pose challenges during biotherapeutic development by compromising drug safety and efficacy. Early assessment of immunogenicity risk is essential to mitigate these risks. Dendritic cells (DCs) are crucial for priming CD4 T cells and necessary for effective antibody production. Therefore, DC internalization has been investigated as a predictive tool for evaluating the immunogenicity risk of biotherapeutics. Previously reported flow cytometry-based DC internalization assays, including our own, have faced several limitations. These limitations included low throughput due to a restricted DC supply from healthy donors, restriction to Fc-containing antibody-based biotherapeutics, and offering only endpoint data. To address these limitations, we explored both direct and indirect labeling approaches using the IncuCyte® real-time imaging platform. Our findings revealed that indirect labeling approach with the commonly used Fab anti-Fc reagents was unsuitable for DC internalization assays due to significant assay background noises and assay bias when evaluating biotherapeutics of different frameworks. In contrast, using direct labeling with Biotracker Orange demonstrated improved predictability, required fewer DCs, and was suitable for high-throughput screening. Additionally, this approach facilitates constant monitoring of the internalization process, offering a comprehensive understanding of cell morphology changes and internalization kinetics. Using a panel of 25 test therapeutic antibodies with known clinical ADA results, the IncuCyte®-based direct labeling assay demonstrated significant improvements in predicting the immunogenicity risk of the tested molecules. The assay demonstrated a high correlation between internalization and clinical immunogenicity risk, outperforming our previous flow cytometry-based results. Overall, the IncuCyte®-based direct labeling assay using Biotracker Orange represents a significant advancement compared to our previous flow cytometry assay. This new technique is a valuable addition to our immunogenicity risk assessment toolbox, and will ultimately lead to more informed decision-making in the early development of biotherapeutics.